Green Energy or Green Colonialism? The Case of Green Hydrogen in Namibia (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
Green hydrogen, promoted by institutions like the International Renewable Energy Agency and the European Union as pivotal to decarbonization, faces criticism through the lens of green colonialism. This paper argues that the energy transition often replicates neo-colonial resource extraction, particularly in Global South nations such as Namibia, where reliance on external technologies and investments risks perpetuating dependency and sidelining local communities. Through an interpretative analysis of global discourse and Namibia’s green hydrogen project, the study underscores the need for a people-centered approach. It proposes justainability—merging justice with sustainability—to prioritize equitable benefits and participatory decision-making, challenging top-down models that neglect socio-environmental equity.
Keywords: Energy transition; green hydrogen; green colonialism; justainability; Namibia